Statistical Learning and Data Sciences : Third International Symposium, SLDS 2015, Egham, UK, April 20-23, 2015, Proceedings - Gammerman, Alexander; Vovk, Vladimir; Papadopoulos, Harris; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Third International Symposium on Statistical Learning and Data Sciences, SLDS 2015, held in Egham, Surrey, UK, April 2015. The 36 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 59 submissions. The papers are organized in topical sections on statistical learning and its applications, conformal prediction and its applications, new frontiers in data analysis for nuclear fusion, and geometric data analysis.
Keywords: Artificial intelligence; Computer software; Database management; Computer science; Information storage and retrieva; Artificial Intelligence; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Database Management; Computation by Abstract Devices; Information Storage and Retrieval